Advanced Control of an Electric Fuel-Oil Pump for Small Turbojet Engines - Ladislav Főző; Rudolf Andoga (Aerospace, 2022)
One way to efficiently control the fuel flow of small turbojet engines is to use direct control of the speed of a suitable electric fuel pump, as opposed to using relief valves. Brushless drive electric (BLDC) motors are suitable for this application, especially for small turbojet engines. This, however, comes with certain problems, which are caused by the backpressure of the engine on the fuel system, delays in data acquisition, sensor noise and so on. This paper presents a comprehensive approach in the methodological design of a dynamic model of a fuel system with a BLDC fuel/oil pump and control algorithms, which can overcome the mentioned problems. Three approaches are evaluated to obtain a stable and precise fuel metering of the engine. This article describes the design of an inverse control model, a standard PID controller and an adaptive fuzzy controller for fuel-flow control during engine operation. The main scientific contribution of the presented study is a simple, yet robust, fuzzy adaptive controller with a lean and comprehensive rule base that can precisely and efficiently meter fuel for small turbojet engines, validated in laboratory conditions using the iSTC-21v turbojet engine.